Evaluation of The Effect of Age of Cultivation of Dumbo Catfish (Clarias gariepinus) on Changes in Pond Water Quality Using Plankton as Bioindicator in Gondosuli Village, Tulungagung Regency - Satria Cahya Febriansyah; Catur Retnaningdyah (University of Brawijaya, 2021)
Catfish is a freshwater fish that is widely cultivated but overfeeding causes organic pollution. This study aims to evaluate the water quality profile based on physicochemical and plankton as bioindicators in catfish ponds in Gondosuli Village, Tulungagung Regency. This type of research was ex post facto by monitoring the physicochemical parameters of water and the structure of the plankton community in control ponds, ponds with catfish aged <1 month, 2-3 months, and 3-4 months each with three replications. Water samples for each pond were measured on the physicochemical water quality included water temperature, conductivity, pH, water transparency, DO, BOD, and turbidity. Plankton identified and analyzed to determine community structure (Abundance, Frequency, Relative Abundance, Relative Frequency, Important Value Index) and biotic index (H', TDI, and %PTV) for water quality. The results of measurements of each physicochemical parameter between locations were statistically analyzed inferentially using a different test. The interaction between the plankton community structure and the physicochemical of water quality was analyzed using biplots. The results showed that ponds with the age of catfish ready to harvest had an impact on decreasing water quality. This condition was indicated by the high organic matter pollution reflected by the high BOD, high turbidity levels, and low DO values. Catfish pond waters quality based on the H' value of plankton community showed that organic matter pollution had not yet occurred. Based on TDI values, catfish pond waters were categorized as poor status (hyper eutrophic) and based on the %PTV index in ponds with catfish age 2-3 and 3-4 months were classified as high levels of organic matter pollution.